Kidney Beam - a cost-effective digital intervention to improve mental health. - Greenwood, S.; Briggs, J.; Walklin, C.; Mangahis, E.; Young, H.; Castle, Ellen; Billany, R.; Asgari, E.; Bhandari, S.; Bishop, N.; Bramham, K.; Burton, J.; et al. (Elsevier, 2024)
Introduction: There is inequity in the provision of physical rehabilitation services for people living with chronic kidney disease (CKD). The Kidney BEAM trial evaluated the clinical value and cost effectiveness of a physical activity digital health intervention (DHI) in CKD. Methods: In a single-blind, 11 center, randomized controlled trial, 340 adult participants with CKD were randomly assigned to either the Kidney BEAM physical activity DHI or a waitlist control. This study assessed the difference in the Kidney Disease Quality of Life Short Form 1.3 Mental Component Summary (KDQoL-SF1.3 MCS) between intervention and control groups at 6-months, and cost-effectiveness of the intervention. Results: At 6-months, there was a significant difference in mean adjusted change in KDQoL MCS score between Kidney BEAM and waitlist control (intention-to-treat adjusted mean: 5.9 [95% confidence interval, CI: 4.4–7.5] arbitrary units [AU], P < 0.0001), and a 93% and 98% chance of the intervention being cost effective at a willingness-to-pay threshold of £20,000 and £30,000 per quality-adjusted life year gained. Conclusion: The Kidney BEAM physical activity DHI is a clinically valuable and cost-effective means to improve mental health-related quality of life (HRQoL) in people with CKD (trial registration no. NCT04872933)